Efficiency of silver nanoparticles against bacterial contaminants isolated from surface and ground water in Egypt (Journal of Advanced Veterinary and Animal Research, 2015)
The bactericidal efficiency of silver nanoparticles (AgNP) was evaluated against bacteria isolated from surface and ground water samples in Egypt. The AgNP were synthesized by typical one-step synthesis protocol, and were characterized using transmission electron microscopy and atomic absorption spectrophotometer. The bactericidal efficiency of AgNP was evaluated by its application in three concentrations i.e., 0.1, 0.05 and 0.01 ppm to water sample, and allowed to interact with bacteria for different duration e.g., 5 min 15 min, 30 min, 1 h and 2 h. Then, the bactericidal efficiency of AgNPs was determined by comparing the counted bacteria before and after the treatments. Higher mean values of total bacterial count (TBC), total coliform count (TCC), and total streptococcal count (TFS) were detected in surface water than in ground water. Also, the results showed that TBC, TCC and TFS exceeded permissible limits. Application of AgNP at different concentration, the number of bacteria in TBC was significantly reduced in all AgNP-exposed samples as compared to the control group (p